Role of Microbial Inoculants on Growth and Development of Jatropha Curcas in Field - , Jamaluddin; Jaiswal, Mithilesh; Pandey, A. K. (Indian Forester, 2012)
Different microbial inoculants were tried to study their effect on the growth and development of Jatropha curcas L. All microbial (mix) inoculants showed response in enhancing the growth of J. curcas in terms of height and collar diameter. Microbial inoculation and mixed inoculation induced flowering while fruiting in 2nd year plants could be recorded only in AM and mixed inoculants of microbes. Though the fruit production was limited but could produce viable seeds. Experiments indicated that the microbial inoculants were more suitable for early flowering and fruiting. It is an important step for enhancing the productivity of this biodiesel plant.